"The Law 11/2007, of Electronic Access of the Citizens to the Public Services" and the use of the free software in the Public Administration. - del Valle García, Diana (Revista General de Información y Documentación, 2013)
The present work analyzes the free software in relation with the Law 11/2007, of Electronic Access of the Citizens to the Public Services. For it, it splits of a study of the Spanish in force legislation and of the European boards and his relation with the application of the free software in the Public Spanish Administration.
Keywords: Administration; electronic Administration; rights of the citizen; Law 11/2007; licenses of software; obligations of the Administration; free software.